Review Paper on the Impact of Climate Change (Temperature, Winds, and Rainfall) on Archaeological Sites in Libya and Mediterranean Basin Countries in Recent Decades - Ashuraks, Aya Nuri; Lahrsh, Zuhur Saad; Altarhony, Retaj Fathy; Abugrean, Elhadi Elmabrouk; Khalifa, Yosof Mohammed (Journal of agricultural, environmental and veterinary sciences, 2025)
Libya, like any other country in North Africa and around the world, is experiencing rapid climate changes that impact various environmental, economic, and social aspects of the country. One of the critical areas affected by these changes is archaeological sites, which are integral to Libya’s cultural and historical heritage. This paper provides a comprehensive review of previous studies in Libya and some studies from Mediterranean countries (Egypt, Tunisia, Morocco, Algeria and Italy) that addressed the impact of climate change on coastal archaeological sites in the region, highlighting the environmental and cultural effects of these changes. The review noted various implications on certain sites, including coastal erosion due to the rise in waves in Apollonia and Tokra in Northeastern Libya, coastal retreat resulting from floods and high winds, and erosion in Susa in the Northeast and Sabratha in the western coastal area. To mitigate those risks, researchers emphasize the need to use barriers such as seawalls or stone blocks to reduce the impact of waves on the shores, and to plant coastal vegetation and trees to protect the soil from erosion. Hence, the authors emphasize the need to raise public awareness about the importance of cultural heritage, which calls for urgent responses from researchers to conduct specialized studies to protect archaeological sites and understand the long-term effects of climate change on these sites. Additionally, there is a need for the government and policymakers to develop and apply sustainable strategies to preserve the heritage and adapt it to these changes.